A execução de boas práticas de atenção ao parto e nascimento em um centro obstétrico do sul do Brasil - Weis, Paola Souza Castro (2023)
In order to guarantee the rights of pregnant women, their autonomy and protagonism, it is necessary for health care to be shared between the multi-professional team and the woman, and in this context there is a need to implement good childbirth care practices. Objective: To analyze the prevalence of good labor and birth care practices in the obstetric center of a university hospital in southern Brazil. Method: This is a cross-sectional quantitative study using documentary data. The study was carried out at a University Hospital in Rio Grande do Sul, and was approved by the Research Ethics Committee (CEP) of the Federal University of Santa Maria (UFSM). The population of this study corresponds to women who gave birth in the obstetric center of that hospital, from January 2020 to December 2021, totaling 2623 women. The information on good labor and birth practices used corresponds to the information collection form for monitoring the indicators instituted at the hospital in October 2019. The indicators on the form are structured into eight topics: identification of the pregnant woman, data related to hospitalization, information related to monitoring labor, delivery data, newborn data, postpartum information, occurrence of sentinel events and hospital discharge data. PASW Statistic (Predictive Analytics Software), version 20 for Windows, was used to analyze the data. We analyzed the institution's good labor and birth care practices, as well as the outcomes following patient care. The analyses showed that there were 2,623 visits to the obstetric center of the referral hospital, with a high frequency of visits to pregnant women considered to be at high risk (80.5%), who were multiparous (63.4%) and had a gestational age of less than 37 weeks (69.1%), as well as a fetus in cephalic presentation (80.4%). The age variable showed a significant association with the variables: risk, parity and type of delivery; while the occurrence of sentinel events showed a statistically significant difference with the Robson Classification variable. The purpose of this study was to help ensure excellent care for pregnant women and a safe birth for their babies.